Environmental, Social, and Governance Awareness and its Impact on Young Customer Loyalty on Bank - Muhammad, Alvin Nur; Firman, Arif; Raharjo, Susilo Toto (Economic and Business Horizon, 2025)
In the era of sustainable finance, awareness of Environmental, Social, and Governance (ESG) principles significantly influences young bank customers, particularly Millennials and Generation Z, who prioritize sustainability. This study investigates the impact of ESG awareness on the loyalty of these young customers. Data were collected from 200 respondents aged 18–35 in urban areas and analyzed using multiple linear regression to evaluate how ESG dimensions environmental protection, social responsibility, and governance practices affect customer loyalty, including satisfaction, trust, and long-term commitment. A case study of Bank Rakyat Indonesia (BRI) Regional Office Padang illustrates how the bank’s ESG initiatives strengthen relationships with young customers and align with Indonesia’s sustainable development goals. The findings reveal a positive and significant relationship between ESG awareness and young customer loyalty, with social and governance factors exerting a greater influence than environmental aspects. This research provides valuable insights for financial institutions seeking to enhance their sustainability strategies and foster long-term customer engagement amid growing demands for social and environmental accountability.